Batu Tumbuk as A New Creation Dance: Art and Culture Preservation Through Time - Muhammad Syafiq Azam; Sumathi Maniam; Muhammad Fazli Taib Saearani (Institut Seni Indonesia Surakarta, 2022)
This research aims to analyze the choreography of the New Creation dance, Batu Tumbuk by Muhaldin Jamin, which was staged in 2015. The term ‘New Creation dance’ refers to the dance that undergoes a process of improvement or refinement that is appropriate to the passage of time but does not affect the traditional values of the community. Hence, this research discusses the Batu Tumbuk dance from the aspect of choreography. The choreographic approach by Minton (1997) is used in this article to discuss the choreographic aspects of the New Creation dance selected. The methodology used for this research was qualitative. Data collection was conducted by using observational methods, unstructured interviews, and library methods. The findings of this research show that the choreography of Batu Tumbuk dance has undergone the creative process of movements and development in terms of composition in the performances presented. Based on the various elements of Malay traditional dance, it is shown that the development processes of Batu Tumbuk dance include actions such as casting, floor patterns and additional props as forms of dance creations. The implications of this research could benefit local choreographers in providing the reference for understanding the terms and concepts of the New Creation dance choreography that continues the original tradition, as a source to be processed and developed in accordance with the passage of time aimed to preserve cultural art heritage.